MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA TENAGA PENDIDIK DI MADRASAH IBTIDAIYAH AL-MUNAWAROH BANDAR LAMPUNG - Fadilah Mustaqim, Dinda; Eti Hadiati; Junaidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Human resource management (HRM) plays a strategic role in improving the performance of educational personnel, which is a key factor in the success of educational institutions. However, the implementation of HRM operational functions at the Islamic elementary school (Madrasah Ibtidaiyah) level has received limited scholarly attention. This study aims to analyze the implementation of human resource management in enhancing the performance of educational personnel at Madrasah Ibtidaiyah Al-Munawaroh Bandar Lampung. This research employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation involving the principal, the vice principal for human resources, the vice principal for student affairs, and the head of administration. Data were analyzed using the stages of data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that the seven operational functions of HRM procurement, development, compensation, integration, maintenance, discipline, and separation have been implemented systematically and collaboratively to improve the performance of educational personnel. The implementation of these functions has contributed to enhancing teachers’ competence, motivation, discipline, loyalty, and professionalism, thereby supporting more effective learning processes and improving the overall quality of education at the madrasah.